Occult Pheochromocytoma and Acute Ischaemic Stroke in Young Adult: Cause or Association - Zeba Siddiqi; Mateen Saboor; Shivesh Singh; Haneen Shah (Case Reports in Clinical Practice, 2024)
Pheochromocytoma is a rare catecholamine-secreting tumours of chromaffin tissues that cause a constellation of symptoms. It is closely associated with endocrine hypertension that can be masked, sustained or paroxysmal leading to hypertensive crisis, resulting in vascular and non-vascular complications and rarely cerebral ischaemia and stroke.A healthy 22 year old male reported with acute Right upper limb(RUL) monoplegia and Motor aphasia for five days with raised blood pressure levels. hypertonia was present, deep tendon reflexes were exaggerated in RUL and Right Plantar was extensor. General and systemic findings were nonsignificant . Routine investigations showed thrombocytosis and M.R.I. Brain was suggestive of acute infarction of Left Parieto-Temporal region. Renal doppler, Carotid Intima Media Thickness, Cerebral Angiogram, 2D-E.C.H.O. and Fundoscopy were normal. AntinuclearAntibody was negative. Contrast CT of abdomen revealed right adrenal mass suggestive of isolated Pheochromocytoma. Vanyl-Mandelic Acid was positive. Patient was stabilised and managed conservatively for 4 weeks followed by adrenalectomy and appropriate medical therapy. Patient is on regular followup and does not seem to require any antihypertensives or any other intervention.Pheochromocytoma is a notorious tumor and a great masquerader specially in young adults. A keen eye, routine checkups and evaluation is the key to detecting and preventing its associated morbidity and mortality.